Solubility and pH of Direct pulp Capping Materials: A Comparative Study. Issue 2 (July 2015) - Poggio, Claudio; Lombardini, Marco; Colombo, Marco; Beltrami, Riccardo; Rindi, Simonetta
Background: The objective of the present study was to compare solubility and pH of 6 direct pulp capping materials. Methods: Specimens of each material – i.e., Dycal, Calcicur, Calcimol LC, TheraCal LC, MTA Angelus and ProRoot MTA – were prepared and immersed in water. Solubility was determined after 24 hours and 2 months and analyzed statistically using a 1-way ANOVA and post hoc Tukey test. pH values were measured 3 and 24 hours after manipulation. Results: All direct pulp capping materials showed low solubility; the pH of tested materials ranged from 10 to 12 and showed a nonsignificant increase/reduction after 24 hours. Conclusions: Within the limitations of this in vitro study, the direct pulp capping materials studied showed different solubility even if no changes were recorded over time. All of the materials showed a very alkaline pH.